2004
DOI: 10.1124/mol.65.4.851
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide (NO) Scavenging and NO Protecting Effects of Quercetin and Their Biological Significance in Vascular Smooth Muscle

Abstract: The flavonoid quercetin reduces blood pressure and endothelial dysfunction in animal models of hypertension. However, the results concerning the relationship between quercetin and NO present a complex picture. We have analyzed the mechanisms involved in the NO scavenging effects of quercetin and its repercussion on NO bioactivity in vascular smooth muscle. Quercetin scavenged NO with apparent zero-order kinetics with respect to NO. This effect was strongly dependent on the O 2 concentrations, so that NO decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…Lopez-Lopez et al [16] reported that quercetin had the ability to reduce blood pressure and endothelial dysfunction in animal models of hypertension. The hypertension and oxidative stress prevention, and the vascular protection effects by chronic treatment of quercetin were also reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez-Lopez et al [16] reported that quercetin had the ability to reduce blood pressure and endothelial dysfunction in animal models of hypertension. The hypertension and oxidative stress prevention, and the vascular protection effects by chronic treatment of quercetin were also reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin has a variety of activities in man. For example, it has been reported to have antioxidant [5][6][7], anti-inflammatory [8], anti-anaphylactic [9], anti-aging [10], antiplatelet aggregatory [11], radioprotective [12], immunomodulatory [13], antidiabetic [14], and anticancer [15] effects, and to improve lipid metabolism [16,17] and endurance exercise capacity [18]. Quercetin also reduces gastrointestinal (GI) intestinal transit in mice [19], induces intestinal smooth muscle relaxation [20], and prevents castor oil-induced diarrhea [21].…”
Section: Introductionmentioning
confidence: 99%
“…2-(4-Carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (c-PTIO) and the flavonoid quercetin are specific NO scavengers [170][171][172]; Uric acid and hesperetin are peroxynitrite scavengers [173,174]. These have been used for determination of RNS involvement as well.…”
Section: Methods To Evaluate the Involvement Of Ros And/or Rns In Phymentioning
confidence: 99%